Antagonistic regulation of trafficking to Caenorhabditis elegans sensory cilia by a Retinal Degeneration 3 homolog and retromer - Martínez-Velázquez, Luis A. (Proc Natl Acad Sci U S A, 2018)
Sensory neurons often possess cilia with elaborate membrane structures that are adapted to the sensory modality of the host cell. Mechanisms that target sensory transduction proteins to these specialized membrane domains remain poorly understood. Here, we show that a homolog of the human retinal dystrophy gene Retinal Degeneration 3 (RD3) is a Golgi-associated protein required for efficient trafficking of a sensory receptor, the receptor-type guanylate cyclase GCY-9, to cilia in chemosensory neurons of the nematode Caenorhabditis elegans. The trafficking defect caused by mutation of the nematode RD3 homolog is suppressed in vivo by mutation of key components of the retromer complex, which mediates recycling of cargo from endosomes to the Golgi. Our data show that there exists a critical balance in sensory neurons between the rates of anterograde and retrograde trafficking of cargo destined for the sensory cilium and this balance requires molecular specialization at an early stage of the secretory pathway.